Hepatic Dendritic Cells in the Development and Progression of Metabolic Steatohepatitis - Méndez-Sánchez, Nahum; Córdova-Gallardo, Jacqueline; Barranco-Fragoso, Beatriz; Eslam, Mohammed (Frontiers in Immunology, 2021)
Metabolic Associated Fatty liver disease (MAFLD) is a global health problem and represents the most common cause of chronic liver disease in the world. MAFLD spectrum goes from simple steatosis to cirrhosis, in between metabolic steatohepatitis with progressive fibrosis, which pathogenesis is not completely understood. Hence, the role of the immune system has become an important fact in the trigger of inflammatory cascades in metabolic steatohepatitis and in the activation of hepatic stellate cells (HSCs). Among, the more studied immune cells in the pathogenesis of MAFLD are macrophages, T cells, natural killer and dendritic cells. In particular, hepatic dendritic cells had recently attracted a special attention, with a dual role in the pathogenesis of MAFLD. These cells have the capacity to switch from a tolerant state to active state inducing an inflammatory cascade. Furthermore, these cells play a role in the lipid storage within the liver, having, thus providing a crucial nexus between inflammation and lipid metabolism. In this review, we will discuss the current knowledge on the dual role of dendritic cells in lipid accumulation, as wells as in the triggering of hepatic inflammation and hepatocytes cell death in metabolic steatohepatitis.